Farmers Adoption of Organic Farming: An Application of the Theory of Planned Behavior and Expectancy Value: การยอมรับของเกษตรกรในการทำเกษตรแบบอินทรีย์: การประยุกต์ใช้ทฤษฎีพฤติกรรมตามแผนและค่าความคาดหวัง - Chaisaeng, Vanich (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ วัตถุประสงค์การวิจัย 1) เพื่อศึกษาพฤติกรรมและองค์ประกอบการยอมรับของเกษตรกรต่อการทำเกษตรแบบอินทรีย์ 2) เพื่อวิเคราะห์แบบจำลองความสัมพันธ์ตัวแปรที่เหมาะสมกับพฤติกรรมการยอมรับของเกษตรกรต่อการทำเกษตรแบบอินทรีย์ จากตัวอย่างเกษตรกร จำนวน 331 คน ด้วยวิธีการลงพื้นที่สัมภาษณ์เกษตรกร สถิติที่ใช้ คือ สถิติอนุมาน เพื่อวิเคราะห์อิทธิพลของตัวแปร ด้วยเทคนิคการวิเคราะห์เส้นทาง และ การวิเคราะห์โมเดลสมการเชิงโครงสร้าง ผลวิจัยพบว่า พฤติกรรมการยอมรับเกษตรแบบอินทรีย์ของเกษตรกร (ADO) มีค่าเฉลี่ยสูงสุดเท่ากับ 5.12 เมื่อเทียบกับพฤติกรรมด้านอื่น ๆ โดยพฤติกรรมการยอมรับเกษตรแบบอินทรีย์มีความสัมพันธ์กับการรับรู้การควบคุมพฤติกรรม (PCB) มีค่าเท่ากับ 0.67 โดยการรับรู้การควบคุมพฤติกรรม มีความสัมพันธ์ทั้งกับทัศนคติและค่านิยม มีค่าเท่ากับ 0.74 และ 0.97 ตามลำดับ ทัศนคติมีค่าความสัมพันธ์กับค่านิยมต่อการทำเกษตรแบบอินทรีย์เท่ากับ 0.82 และค่านิยมมีค่าความสัมพันธ์กับพฤติกรรมความตั้งใจทำเกษตรแบบอินทรีย์เท่ากับ 0.53 ทั้งนี้ความสัมพันธ์ของพฤติกรรมทุกคู่มีนัยสำคัญทางสถิติที่ระดับ 0.01 ผลที่ได้หลังปรับตัวแบบสมการโครงสร้าง พบว่า สอดคล้องกับข้อมูลเชิงประจักษ์ ทำให้ยอมรับสมมติฐานหลัก 2 สมมติฐาน คือ ค่านิยมมีอิทธิพลเชิงบวกต่อความตั้งใจทำเกษตรแบบอินทรีย์ (H2) มีค่าเท่ากับ 1.67 และการรับรู้การควบคุมพฤติกรรม (PBC) มีอิทธิพลเชิงบวกต่อการยอมรับการทำเกษตรแบบอินทรีย์ (H4) มีค่าเท่ากับ 1.50 อย่างนัยสำคัญทางสถิติที่ระดับ 0.01 นั่นคือ พฤติกรรมการยอมรับจึงเป็นกระบวนการที่เกิดขึ้นทางจิตใจซึ่งมีกระบวนการที่คล้ายกับการเรียนรู้ และมีผลต่อการตัดสินใจยอมรับการทำเกษตรแบบอินทรีย์ ได้ในอนาคต ABSTRACT The research objectives of the present study were the following: 1) to study the behaviors and components of farmers’ adoption of organic agriculture; and 2) to analyze a model of the relationship of the variables that are appropriate for farmers’ behavior toward organic agriculture by surveying and collecting data from 331 samples in an agricultural farm, interviewing the targeted farmers. Inferential statistics were used to analyze the influence of the variables, using the path analysis technique and structural equation modeling. The results of the research showed that the adoption behavior of the organic agriculture of farmers had the highest average of 5.12 when compared with other behaviors. The adoption behavior regarding organic agriculture was correlated with the perceived control behavior (PCB) of 0.67 and PCB was correlated with attitudes and subjective norms at 0.74 and 0.97, respectively. Further, the attitudes and subjective norms regarding organic agriculture were correlated at 0.82. Subjective norms and intentions to use organic agriculture had a relationship value of 0.53. However, the behavioral relationships of all pairs were statistically significant at the level of 0.01. The results of the post-adaptation study showed that the modified model of the equation was consistent with the empirical data after the model adjustment. This made the main hypothesis accepted 2 hypotheses. The results revealed that the subjective norm had a positive influence on the intentions of the organic agriculture of famers (H2), equivalent to 1.67, and was statistically significant at the 0.01 level; and perceived behavior control had a positive influence on the adoption of organic agriculture (H4), equivalent to 1.50, and was statistically significant at the level of 0.01. That is, the behavior of adoption is a psychological process, similar to learning, and can influence the decision to adopt organic agriculture in the future.